Comparison of the Energy Properties of Sunflower Stalk Fibers for Solid Biofuel Production - Diana Kindzera; Viktoria Kochubei (Journal of Chemistry)
The possibility of producing solid biofuels from sunflower stalks, an agricultural residue that is currently underused, has been investigated. By cutting the tissues along the sunflower stalks and mechanical grinding, samples were obtained, namely, sunflower stalk rind (SSR), sunflower stalk intermediate (SSI), and sunflower stalk pith (SSP), and by grinding sunflower stalks, as a whole, sunflower stalk general (SSG) sample was obtained. Different chemical compositions of sunflower stalk samples, according to the cellulose, hemicellulose, and lignin, influenced their thermal decomposition behavior. The lignin contents were found to be 19.8 wt.% in the SSR, 16.6 wt.% in the SSI, 3.8 wt.% in the SSP, and 15.8 wt.% in the SSG samples. The results were useful to forecast different calorific values of samples—higher for SSR, SSI, and SSG compared to the SSP sample. According to the results of comprehensive thermal analysis, the thermal decomposition of all samples occurred in five stages, different in their temperature ranges for every individual sample and mass loss of substances. By DTA curves comparison, the highest calorific value for the SSB sample, lower for the SSI and the SSG samples, and the lowest for the SSP sample were established. Calorific values determined by the calorimetric method were 18.2 MJ/kg for the SSR, 14.7 MJ/kg for the SSІ, 7.4 MJ/kg for the SSP, and 14.2 MJ/kg for the SSG samples. The results of the experimental determination of ash content showed 8.8 wt.% for SSR, 7.6 wt.% for SSI, 16.1 wt.% for SSР, and 10.2 wt.% for SSG samples. Due to the adequate calorific value, but the excessive level of ash content, the rind, intermediate segments of sunflower stalks, and sunflower stalks as a whole were recommended as components of solid composite fuel based on woody biomass.